Second time around [large type] - Carlson, Melody (Thorndike Press large print Christian fiction series., 2023)
"When empty nester Mallory Farrell inherits her grandmother's run-down tourist shop in Seaport, Oregon, it seems the only sensible thing to do is to sell it. But when her former secret crush, Grayson Matthews, wants to buy the property in order to complete his plans to redevelop the funky town's business district into a soulless, cookie-cutter outdoor mall, Mallory digs in her heels and decides to renovate the property herself. With a lot of hard work and a little bit of help, Mallory makes incredible progress turning the store into an eclectic home décor shop called Romancing the Home--all while trying to ignore the depressing and decrepit apartment she's living in on the second floor. When the shop catches the eye of a popular renovation TV show producer, Mallory is thrilled--until it becomes clear that her apartment is to be part of the segment as well. She's tempted to abandon her dreams and the town under a cloud of shame. But perhaps there's more to Grayson than meets the eye. Can he swallow his pride, change his plans, and help Mallory romance her own home--and possibly her life?"--